2018
DOI: 10.3390/cosmetics5040057
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Metals in Several Brands of Lipstick and Face Powder Present on Polish Market

Abstract: Cosmetics still retain their brilliant effect, but public concern about their toxicity has become a hot issue. Trace amounts of toxic heavy metals can be either intentionally added to cosmetics or present as impurities in the raw materials. We therefore assessed the levels of lead, nickel, copper, zinc and iron in six brands of lipstick and six brands of cosmetic powder that are widely available in local Polish markets. The cosmetics were digested and analyzed for the metals using flame atomic absorption spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 20 publications
3
35
2
Order By: Relevance
“…Although the term 'heavy metals' poorly describes the nature of metals in scientific terms [8], in this present study, both toxic metals (Ag, Cd, Hg, Pb and Sn) and essential microminerals (Cr, Cu, Ni, Zn, Fe and Mn) were grouped under this general definition. Previous studies showed that metals such as Pb and Cu are present in toothpastes and other cosmetic products [1,9]. These impurities may reach the general circulation in the body leading to detrimental effects [10,11].…”
Section: Heavy Metal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Although the term 'heavy metals' poorly describes the nature of metals in scientific terms [8], in this present study, both toxic metals (Ag, Cd, Hg, Pb and Sn) and essential microminerals (Cr, Cu, Ni, Zn, Fe and Mn) were grouped under this general definition. Previous studies showed that metals such as Pb and Cu are present in toothpastes and other cosmetic products [1,9]. These impurities may reach the general circulation in the body leading to detrimental effects [10,11].…”
Section: Heavy Metal Analysismentioning
confidence: 99%
“…Although in most cases, cosmetics are applied by a category of a population, the use of toothpastes on a daily basis to maintain oral hygiene is cosmopolitan. Consequently, the daily constant ingestion of heavy metals and xenobiotics raises safety issues [1]. This is because many countries do not regulate the presence of these heavy metals and xenobiotics in cosmetic products.…”
Section: Introductionmentioning
confidence: 99%
“…Vella et al, 2019 reported presence of lead in toothpastes were beyond limit of US and EU standards [13]. According to Panico et al, 2019 PEGs (favorably used as penetration enhancers) may contain residual impurities like lead, iron, cobalt, nickel, cadmium, arsenic [14]. Łodyga-Chruścińska et al, 2018 detailed nearness of lead and nickel in lipsticks and powders at level restricted by European guideline in Polish market [15].…”
Section: Introductionmentioning
confidence: 99%
“…Prompt treatment of microbial keratitis is important to prevent vision loss [49] . Łodyga-Chruścińska et al, 2018 reported presence of lead and nickel in lipsticks and powders at level prohibited by European regulation in Polish market [50] . However, several studies revealed that human exposure to heavy metals and many other potential toxins were not only from food, water, mining activity, toys, plastics, jewelry, but also from personal care products.…”
Section: Introductionmentioning
confidence: 99%